Anti-GFAP Antibody-Associated Hypertrophic Pachymeningitis - Tan, Chengbing; Zhong, Min; Yao, Zhengxiong; Hong, Siqi; Jiang, Li; Jiang, Yan (Neuropediatrics, 2022)
Background Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is an inflammatory central nervous system (CNS) disorder that usually presents as steroid responsive encephalitis, meningitis, myelitis, or meningoencephalomyelitis. Hypertrophic pachymeningitis (HP) is an uncommon disorder that causes a localized or diffuse thickening of the dura mater. Depending on the etiology, HP can be idiopathic or secondary to a wide variety of other diseases. There are no reports of autoimmune GFAP astrocytopathy presenting as HP.Methods In this case report, we describe a rare case of pediatric HP possibly associated with anti-GFAP antibody.Results A 13-year-old previously healthy girl presented with headache for nearly 8 months with left-sided peripheral facial palsy and left-sided abductor nerve palsy in the second month of course. Magnetic resonance imaging (MRI) of the brain revealed contrast enhancement of hypertrophic dura mater. Anti-GFAPα antibodies were positive in serum and cerebrospinal fluid. The patient improved clinically after steroid treatment with partial resolution of abnormal intracranial MRI lesions.Conclusion The present study suggests that HP may be one of the clinical phenotypes for autoimmune GFAP astrocytopathy or GFAP antibody is a biomarker for HP.
Keywords: autoimmune glial fibrillary acidic protein astrocytopathy; hypertrophic pachymeningitis; autoimmune inflammation; MRI